Benign hilar bile duct strictures resected as perihilar cholangiocarcinoma. Issue 11 (6th August 2019) - Otsuka, S; Ebata, T; Yokoyama, Y; Igami, T; Mizuno, T; Yamaguchi, J; Onoe, S; Watanabe, N; Shimoyama, Y; Nagino, M
Abstract: Background: Differentiation between perihilar cholangiocarcinoma (PHCC) and benign strictures is frequently difficult. The aim of this study was to investigate the incidence and long-term outcome of patients with tumours resected because of suspicion of PHCC, which ultimately turned out to be benign (malignancy masquerade). Methods: Patients who underwent surgical resection with a diagnosis of PHCC between 2001 and 2016 were reviewed retrospectively. Results: Among 707 consecutive patients, 685 had PHCC and the remaining 22 (3·1 per cent) had benign biliary stricture. All patients with benign disease underwent major hepatectomy, with no deaths. Preoperative histological assessment using bile duct biopsy or aspiration cytology had a high specificity (90 per cent), low sensitivity (62 per cent) and unsatisfactory accuracy (63 per cent). Despite the increasing use of histological assessment, the incidence of benign strictures resected did not decrease over time, being 0·9 per cent in 2001–2004, 4·0 per cent in 2005–2008, 3·8 per cent in 2009–2012 and 2·9 per cent in 2013–2016. The final pathology of benign strictures included IgG4-related sclerosing cholangitis (9 patients), hepatolithiasis (4), granulomatous cholangitis (3), non-specific chronic cholangitis (3), benign strictures after cholecystectomy (2), and a benign stricture possibly caused by parasitic infection (1). The 10-year overall survival rate for the 22 patients with benign stricture was 87 per cent, without recurrence of biliary stricture. Conclusion: The incidence of benign strictures resected as PHCC as a proportion of all resections was relatively low, at 3·1 per cent. Currently, unnecessary surgery for suspected PHCC is unavoidable. Graphical Abstract: A total of 707 consecutive patients underwent resection following diagnosis of presumed perihilar cholangiocarcinoma; 685 of these patients had cholangiocarcinoma, and the remaining 22 (3·1 per cent) had benign biliary stricture. Despite the increasing use of preoperative histological assessment, the incidence of benign stricture resection was unchanged over time. Does not happen that often